PRODUKSI SERASAH HUTAN LARANGAN ADAT DESA JAKE KABUPATEN KUANTAN SINGINGI SEBAGAI RANCANGAN HANDOUT PADA MATERI EKOSISTEM DI SMA KELAS X - Solikin, Muhammad; Fauziah, Yuslim; Suwondo, Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the amount of litter production in the traditional Forest District of Jake Village, Kuantan Singingi Regency and produce a learning handout design on ecosystem material in class X high school. The research took place in April-May 2019. The study consisted of two stages, namely the analysis stage of average forest litter production and the handout design stage. The stage of field data collection was carried out with descriptive research, data collection by survey methods, determination of sampling points by purposive random sampling. The parameters in this research are the composition of Jake Indigenous Forest Littering Forest and the supporting parameters in the form of environmental factors that affect litter production. The results of the study were obtained by calculating the production of Jake Indigenous Forest Prohibition Litter to meet the needs of organic materials needed in the forest ecosystem. Based on an analysis of the potential results of the research, a handout of biogeneemical cycle material was designed for Biology learning in high school grade XKey Words: Litter fall, Forest, Handout